Efektivitas Penerapan Absensi Finger Print pada Lembaga Pendidikan Perkebunan Medan - Ulfi Syafitri; Usman Tarigan; Beby Masitho Batubara (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2021)
This study aims to determine the effectiveness of the application of finger print attendance in improving employee work discipline at the Medan Plantation Education Institute in terms of attendance levels, convenience and comfort in the attendance process, providing complete information / reports to leaders, and applying finger print attendance to make it easier for superiors. to see the level of attendance and work discipline of each employee. The results showed that the application of finger print attendance has not been able to improve employee work discipline, seen from the target achievement after the application of finger print attendance has not been achieved, where it is known that many employees are not disciplined in work such as arriving late to the office. Adaptability, employees already understand the rules for using finger print attendance and are able to adjust from manual attendance to finger print attendance. Job satisfaction for employees, the Medan Plantation Education Institute has provided comfort and motivation for employees to improve their performance. While the responsibilities of the employees of the Medan Plantation Education Institute have not increased, there are still many employees who come late to the office